2021
DOI: 10.1136/bmjopen-2021-051192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgeon and anaesthesiologist sex on patient outcomes after cardiac surgery: a population-based study

Abstract: BackgroundEffective teamwork between anaesthesiologists and surgeons is essential for optimising patient safety in the cardiac operating room. While many factors may influence the relationship between these two physicians, the role of sex and gender have yet to be investigated.ObjectivesWe sought to determine the association between cardiac physician team sex discordance and patient outcomes.DesignWe performed a population-based, retrospective cohort study.Participants and settingAdult patients who underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The importance of patient-provider relationships, including those developed with female healthcare providers, has been shown to affect health outcomes, such as discussing reproductive goals with healthcare providers and sexual and perinatal wellbeing among women living with HIV [ 12 , 36 ]. Healthcare provider gender has been shown to predict health outcomes outside of HIV care [ 37 , 38 ]. Women living with HIV who have good relationships with their care providers may be more likely to remain engaged in and feel safe, supported, and satisfied with their HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of patient-provider relationships, including those developed with female healthcare providers, has been shown to affect health outcomes, such as discussing reproductive goals with healthcare providers and sexual and perinatal wellbeing among women living with HIV [ 12 , 36 ]. Healthcare provider gender has been shown to predict health outcomes outside of HIV care [ 37 , 38 ]. Women living with HIV who have good relationships with their care providers may be more likely to remain engaged in and feel safe, supported, and satisfied with their HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…Research demonstrates that women’s cardiac outcomes are poorer if there is a physician-patient gender discordance (Lau et al, 2021 ). In contrast, Sun et al ( 2021 ) found no gender discordance difference in length of stay or mortality but that female patients with a female surgeon (or a female surgeon and anaesthetist dyad) had shorter lengths of stay, confirming findings by Greenwood et al ( 2018 ) that male physicians treating female patients was associated with poorer outcomes, not gender discordance per se. Education is recommended for healthcare professionals and for women to be empowered to self-advocate, however it is critical to ensure women do not experience negative fall-out if their efforts in self-advocating develop faster than education and cultural changes within which they seek care (Stehli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 74%
“…Ontario is the most populous province in Canada, with about 14.6 million residents, and is ethnically diverse. 10 Ontario operates a publicly funded health care system that reimburses all covered services and clinicians. All centres in Ontario performing cardiac surgical procedures were included.…”
Section: Methodsmentioning
confidence: 99%
“…21,23,29,30 Frailty is defined by the Hospital Frailty Risk Score, a multidimensional frailty instrument that was validated using routinely collected hospital admissions data of patients aged 75 years or older from the United Kingdom. 31,32 This score ranges between 0 and 173.1 points and is stratified by low risk (< 5), intermediate risk [3][4][5][6][7][8][9][10][11][12][13] and high risk (> 15). 31…”
Section: Covariatesmentioning
confidence: 99%